Health Manpower Systems: An Application of Simulation to the Design of Primary Health Care Teams - Uyeno, Dean H. (Management Science, 1974)
A method was developed for the evaluation of alternative primary health care team compositions and for the examination of skill levels for new categories of personnel. This procedure determines the appropriate composition of primary health care teams for differing demand levels and facility availabilities. A simulation model of a general primary health care delivery unit was developed as part of this procedure. This simulation model, given demand schedules, team compositions, and facility levels, produces information relating to the efficiency and effectiveness of that alternative. An application of the simulation model and the evaluation procedure was made to the area of pediatrics. A time study was taken of pediatric office practice. The data gathered therein were analyzed and used to create various demand schedules. Task-capability lists were created for various proposed categories of allied child health personnel, and these personnel were incorporated into various alternative team compositions and tested against varying facility and demand levels. Results indicate there are instances where a team structure is inappropriate and that the first member added to aid the physician is probably a person to assume lower level repetitive tasks.